AAS, growth hormone, and insulin abuse: psychological and neuroendocrine effects - Michael R Graham; Peter Evans; Bruce Davies; Julien S Baker (Dove Medical Press, 2008)
Michael R Graham1, Peter Evans2, Bruce Davies1, Julien S Baker11Health and Exercise Science Research Unit, Faculty of Health Sport and Science, University of Glamorgan, Pontypridd, Wales, United Kingdom; 2Royal Gwent Hospital, Newport, Gwent, United KingdomAbstract: The nontherapeutic use of prescription medicines by individuals involved in sport is increasing. Anabolic-androgenic steroids (AAS) are the most widely abused drug. Much of our knowledge of the psychological and physiological effects of human growth hormone (hGH) and insulin has been learned from deficiency states. As a consequence of the Internet revolution, previously unobtainable and expensive designer drugs, particularly recombinant human growth hormone (rhGH) and insulin, have become freely available at ridiculously discounted prices from countries such as China and are being abused. These drugs have various physiological and psychological effects and medical personnel must become aware that such prescription medicine abuse appears to be used not only for performance and cosmetic reasons, but as a consequence of psychological pre-morbidity.Keywords: AAS, cosmesis, growth hormone, insulin, performance, strength